2020
DOI: 10.3389/fneur.2020.555202
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis and Hospital Emergency Management for Fastlane Treatment of Central Nervous System Infection Under the COVID-19 Epidemic in Changsha, China

Abstract: Importance: Corona virus disease 2019 (COVID-19) has long latent period, strong infectivity, and non-specific symptoms and signs in the upper respiratory tract. Some initial neurological symptoms appear, including dizziness, headache, seizures, slurred speech, disturbance of consciousness, and limb paralysis among a few COVID-19 patients, which share similar manifestations with central nervous system (CNS) infection. Improving the diagnostic efficiency of suspected CNS infection patients on the basis of preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…The World Health Organization (WHO) named the disease as coronavirus disease 2019 (COVID-19), and the International Committee on the Taxonomy of Viruses named the virus as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 1 Respiratory droplets and direct contact were the main transmission routes. 2 A study of 1354 Canadian adults in early February 2020 showed ~40% of the participants were worried or very worried about SARS-CoV-2, even with only four confirmed cases in Canada at that time.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) named the disease as coronavirus disease 2019 (COVID-19), and the International Committee on the Taxonomy of Viruses named the virus as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 1 Respiratory droplets and direct contact were the main transmission routes. 2 A study of 1354 Canadian adults in early February 2020 showed ~40% of the participants were worried or very worried about SARS-CoV-2, even with only four confirmed cases in Canada at that time.…”
Section: Introductionmentioning
confidence: 99%
“…It is found to cause attention deficit hyperactivity disorder and neurodevelopmental disorders in offspring [75,76]. Recent human studies confirmed that the administration of ACEIs or ARBs did not increase the expression of ACE2 [77][78][79]. Therefore, ACEIs and ARBs can be used as anti-hypertensive medications in pregnant women with hypertension despite COVID-19 infection.…”
Section: Treatment Of Pregnant Women With Cns Symptomsmentioning
confidence: 99%
“…In December 2019, an outbreak of a novel coronavirus pneumonia (NCP) occurred in Wuhan, Hubei province, China, and it rapidly spread to different provinces in China, as well as countries in Southeast Asia, Europe, North America, and many others (1). The Chinese National Health Commission has listed NCP as a category B infectious disease, and the management measures for category A infectious diseases were adopted, indicating that new discovered cases are required to be reported within 2 and 6 h in the city and countryside, respectively (2,3). According to the World Health Organization (WHO), the official name of the disease is coronavirus disease 2019 (COVID-19) and according to the International Committee on Taxonomy of Viruses, the virus is called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (4, 5).…”
Section: Introductionmentioning
confidence: 99%